2018
DOI: 10.3390/medicines5030087
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of Green Tea and the Underlying Molecular Mechanisms in Bladder Cancer

Abstract: Green tea and green tea polyphenols (GTPs) are reported to inhibit carcinogenesis and malignant behavior in several diseases. Various in vivo and in vitro studies have shown that GTPs suppress the incidence and development of bladder cancer. However, at present, opinions concerning the anticancer effects and preventive role of green tea are conflicting. In addition, the detailed molecular mechanisms underlying the anticancer effects of green tea in bladder cancer remain unclear, as these effects are regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 115 publications
(149 reference statements)
1
39
0
Order By: Relevance
“…Nevertheless, high percentage of cell mortality was observed after irradiation and 24‐h incubation (Figure URE 8), especially for Pt NPs synthesized by green chemistry methods. Green tea has been reported to prevent carcinogenesis . It has also been reported that catechins from green tea have a synergetic effect with anticancer drugs in tertiary cancer prevention .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, high percentage of cell mortality was observed after irradiation and 24‐h incubation (Figure URE 8), especially for Pt NPs synthesized by green chemistry methods. Green tea has been reported to prevent carcinogenesis . It has also been reported that catechins from green tea have a synergetic effect with anticancer drugs in tertiary cancer prevention .…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, anticancer properties of green tea have been reported, which are attributed to the presence of polyphenols, such as epicatechin, epigallocatechin, epicatechin‐3‐gallate, and epigallocatechin‐3‐gallate . Several studies have shown that drinking green tea can prevent carcinogenesis and the development of various types of cancers Moreover, green tea polyphenols are responsible for the regulation of different cancer‐related processes and factors, including DNA methylation and microRNA, histone, and protein modification . Recently, it was shown that green tea plays a very important role in cancer prevention .…”
Section: Resultsmentioning
confidence: 99%
“…The phenolic mixes of green tea with the most astounding focus are gallic acid, gallocatechin, catechin, epicatechin, epigallocatechin, epicatechin gallate, epigallocatechin gallate, p-coumaroylquinic corrosive and gallocatechin-3gallate (Shishikura and Khokhar, 2005;Kwon et al, 2015;Riley et al, 2018). Green tea likewise contains dense and hydrolyzable tannins (Okuda and Ito, 2011;McAlpine et al, 2016) and has the most astounding centralization of polyphenols contrasted with different teas, including epigallocatechin gallate (EGCG), which might be the reason green tea can prompt apoptotic cell passing in malignant growth than different teas (Lin et al, 2003;Riley et al, 2018;Miyata et al, 2018). Green tea polyphenols have been exhibited against malignant growth action in various investigations that could be intervened by the antioxidant or pro-oxidant system in various rats models of human disease (Davalli et al, 2012;Naponelli et al, 2017;Fujiki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Green tea polyphenols have been exhibited against malignant growth action in various investigations that could be intervened by the antioxidant or pro-oxidant system in various rats models of human disease (Davalli et al, 2012;Naponelli et al, 2017;Fujiki et al, 2018). These polyphenols, for example, EGCG hinders cell feasibility and actuate apoptosis in various malignant growth cell lines, for example, osteogenic sarcoma (Ji et al, 2006), lymphoblastoid cells (Noda et al, 2007), leukemia cells (Nakazato et al, 2005), melanoma cells (Nihal et al, 2005), immune system microorganisms (Li et al, 2000), antibladder cancer (Miyata et al, 2018) and laryngeal carcinoma (Lee et al, 2010). Green tea polyphenols have appeared to lessen the separation of malignant growth cells into slower multiplying cells (Zhou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, none of three cohort studies and only one out of four case-control studies reviewed in one of the articles cited by Dr. Ranjan did show an inverse association between green tea drinking and bladder cancer risk in humans. 4 Interestingly, in another article cited by Dr. Ranjan, 5 no association between green tea drinking and gastric cancer was observed in prospective cohort studies (relative risk 1.05; 95% confidence interval [CI], 0.90-1.21), and an inverse association was observed only in case-control studies (odds ratio, 0.84; 95% CI, 0.74-0.95); the dose-response analysis was mostly based on case-control studies. It should be noted that although case-control studies are important to study very rare diseases or to generate hypotheses, because of a strong probability of recall bias and higher possibility of selection bias in case-control studies, prospective cohort studies provide more reliable information on the association between dietary factors and cancer.…”
mentioning
confidence: 99%